MT Moorosi's past and present : interpreting San rock art at MTM 1 site in the Quthing District of Lesotho - Mokhanya, Sello (My University, 2009)
The most significant challenge facing rock art research in Lesotho is to provide meaning to San rock paintings that abound in the country. In the past rock art researchers in Lesotho appear to have focused on site identification and documentation. While there are many sites that needed to be interpreted, this challenge was made more difficult by the Euro-centric approach of many researchers. In the absence of reliable interpretive theories, the challenge of finding meaning in San rock paintings remains a forlorn hope. Drawing on San ethnography and neuropsychological research, approaches that have been demonstrated as useful interpretive tools in southern Africa, I take up this challenge of interpreting a San rock art site from Lesotho. While concerned with one site known as MTM 1 in south-eastern Lesotho, in the Quthing District, I use an ethnographic approach and neuropsychological research as tools for understanding paintings at MTM 1. In using these two approaches to interpret rock paintings, it becomes evident that San rock art in this region can best be understood through the use of these approaches. This work, then contributes to the few efforts by previous researchers to interpret rock paintings in Lesotho.